2020
DOI: 10.48550/arxiv.2010.16099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MLatticeABC: Generic Lattice Constant Prediction of Crystal Materials using Machine Learning

Abstract: Lattice constants such as unit cell edge lengths and plane angles are important parameters of the periodic structures of crystal materials. Predicting crystal lattice constants has wide applications in crystal structure prediction and materials property prediction. Previous work has used machine learning models such as neural networks and support vector machines combined with composition features for lattice constant prediction and has achieved a maximum performance for cubic structures with an average R 2 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In many cases, the radius ratio plays an important role. At present, the space group 51,52 and lattice constants 53,54 of crystal structures can be predicted, and the contact map of a given composition can also be predicted by the deep learning method. 24 With the development of machine learning algorithms, we expect that the various inputs required by our multiobjective genetic algorithm for crystal structure reconstruction can be predicted with high precision, so as to allow our CMCrystalMOO to achieve a high-quality crystal structure prediction with only a given composition.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the radius ratio plays an important role. At present, the space group 51,52 and lattice constants 53,54 of crystal structures can be predicted, and the contact map of a given composition can also be predicted by the deep learning method. 24 With the development of machine learning algorithms, we expect that the various inputs required by our multiobjective genetic algorithm for crystal structure reconstruction can be predicted with high precision, so as to allow our CMCrystalMOO to achieve a high-quality crystal structure prediction with only a given composition.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the radius ratio plays an important role. At present, the space group [51,52] and lattice constants [53,54] of crystal structures can be predicted, and the contact map of a given composition can also be predicted by the deep learning method [24]. With the development of machine learning algorithms, we expect that the various inputs required by our multi-objective genetic algorithm for crystal structure reconstruction can be predicted with high precision, so as to allow our CMCrystalMOO achieves high-quality crystal structure prediction with only a given composition.…”
Section: Discussionmentioning
confidence: 99%
“…After inspecting the generated structures by the GAN, it was found that the generated lattice parameter a was often not good enough, leading to overlapping atom clusters. To address this issue, an additional post-processing step introduced to predict the lattice length a using a composition based machine learning model that the authors recently developed, [43] which achieved a R 2 score of 0.979 for cubic lattice a prediction.…”
Section: Cubicgan Frameworkmentioning
confidence: 99%